Relative Financial Deprivation and Financial Satisfaction among Minimum Wage Earners in Türkiye: A Serial Mediation Analysis - Korhan Karacaoğlu; Göknur Ersarı Taşkesen (Ekonomi, Politika & Finans Araştırmaları Dergisi)
The research is a behavioral finance-based study that examines the financial difficulties experienced by minimum wage earners in Turkey from a psychological perspective. In this context, the study explains the financial difficulties experienced by minimum wage earners based on the theory of relative deprivation. The aim of the study is to determine the financial difficulties experienced by minimum wage earners and the psychological effects of this situation. To achieve this goal, the study examines the serial mediator role of financial self-efficacy and financial anxiety in the relationship between relative financial deprivation and financial satisfaction. In this context, a survey was conducted among 633 minimum wage earners in Turkey. The findings of the study indicate that minimum wage earners in Turkey experience relative financial deprivation, which in turn reduces their financial satisfaction. Furthermore, the study revealed that financial self-efficacy and financial anxiety act as mediators in the relationship between relative financial deprivation and financial satisfaction, with each acting independently. However, the study also demonstrated that financial self-efficacy and financial anxiety do not act in a serial mediation role in the relationship between financial deprivation and financial satisfaction.